2016
DOI: 10.1007/s00234-016-1678-x
|View full text |Cite
|
Sign up to set email alerts
|

Duplex-assisted carotid artery stenting without administration of contrast medium for patients with chronic kidney disease or allergic reaction

Abstract: Duplex-assisted CAS without administration of contrast medium could be an alternative option in selected patients deemed to be at high risk for renal failure from nephrotoxic contrast medium or who have an allergy to contrast medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In contrast, carotid duplex, which has the benefit of excellent temporal resolution, is suitable for visualizing the mobility of ISP [14]. Therefore, carotid duplex can not only be used as an adjunctive imaging technique for reducing or avoiding the use of a contrast medium [6][7][8] but also can be used to complement IVUS for the characterization of ISPs. Radiation exposure of a sonographer, which seems to be a major concern, can be prevented by stopping fluoroscopic imaging during carotid duplex scanning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, carotid duplex, which has the benefit of excellent temporal resolution, is suitable for visualizing the mobility of ISP [14]. Therefore, carotid duplex can not only be used as an adjunctive imaging technique for reducing or avoiding the use of a contrast medium [6][7][8] but also can be used to complement IVUS for the characterization of ISPs. Radiation exposure of a sonographer, which seems to be a major concern, can be prevented by stopping fluoroscopic imaging during carotid duplex scanning.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have reported the usefulness of adjunctive carotid duplex in CAS, particularly in minimizing iodinated contrast usage [6][7][8]. Here, we present the case of a patient with ISP with mobile features, which was detected using extravascular ultrasonography during the procedure of duplex-assisted CAS without the use of a contrast medium.…”
Section: Introductionmentioning
confidence: 94%
“…Non-enhanced MRA of the aortic arch and iliac-femoral artery was performed preoperatively to evaluate the access route, as previously reported. 4 First, we performed our previously reported ultrasonographically-guided CAS 4 on the patient's right side, without any complication. MRA confirmed the bilateral severe VAOS, and showed the bilateral absence of (Figure 3A,B) and aspirating the blood (about 100 mL) to remove the debris, the balloon and EPD were retracted under ultrasonographic monitoring.…”
Section: Case Reportmentioning
confidence: 99%
“…Several studies have reported ultrasonographic guidance of carotid artery stenting (CAS) without contrast medium. [3][4][5] However, ultrasonographic imaging of the vertebral artery origin may be difficult because it can be located deep in the chest. Based on our experience with ultrasonographic guidance of CAS, 4 we applied this technique to VAOS stent placement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation